A critical review of upadacitinib for the treatment of adults with moderately to severely active ulcerative colitis. (1st February 2023) - Law, Cindy C.Y.; Kayal, Maia; Mehandru, Saurabh; Colombel, Jean-Frédéric
ABSTRACT: Introduction: Upadacitinib is a selective janus kinase 1 inhibitor. In March 2022, upadacitinib was approved by the US Food and Drug Administration for the management of moderately to severely active ulcerative colitis (UC) in those who have had an inadequate response or intolerance of tumor necrosis factor inhibitors. It is also approved for the treatment of psoriatic arthritis, atopic dermatitis, rheumatoid arthritis, ankylosing spondylitis, and non-radiographic axial spondyloarthritis. Areas Covered: The aim of this article is to review the mechanism of action of upadacitinib, clinical data regarding its efficacy in treating UC, and safety information. Expert Opinion: Upadacitinib is superior to placebo in inducing and maintaining both clinical and endoscopic remission in moderately to severely active UC. Its strengths include once daily oral route of administration, low risk of immunogenicity, rapid onset, and efficacy in patients with previous failure of biologic therapy. The use of upadacitinib has been limited due to safety concerns surrounding JAK inhibitors. Phase 3 clinical trials recorded more cases of herpes zoster infection and venous thromboembolism in patients with UC treated with upadacitinib compared to placebo. Ongoing long-term safety studies will provide much needed clarity. Further research is also required to define the positioning of upadacitinib in treatment algorithms.